Isolation and characterisation of the cDNA encoding a glycosylated accessory protein of pea chloroplast DNA polymerase. - Gaikwad, A (1999)
The cDNA encoding p43, a DNA binding protein from pea chloroplasts (ct) that binds to cognate DNA polymerase and stimulates the polymerase activity, has been cloned and characterised. The characteristic sequence motifs of hydroxyproline-rich glyco-proteins (HRGP) are present in the cDNA corres-ponding to the N-terminal domain of the mature p43. The protein was found to be highly O-arabinosylated. Chemically deglycosylated p43 (i.e. p29) retains its binding to both DNA and pea ct-DNA polymerase but fails to stimulate the DNA polymerase activity. The mature p43 is synthesised as a pre-p43 protein containing a 59 amino acid long transit peptide which undergoes stromal cleavage as evidenced from the post-translational in vitro import of the precursor protein into the isolated intact pea chloroplasts. Surprisingly, p43 is found only in pea chloroplasts. The unique features present in the cloned cDNA indicate that p43 is a novel member of the HRGP family of proteins. Besides p43, no other DNA-polymerase accessory protein with O-glycosylation has been reported yet.